2019
DOI: 10.3390/cells8101246
|View full text |Cite
|
Sign up to set email alerts
|

Gγ and Gα Identity Dictate a G-Protein Heterotrimer Plasma Membrane Targeting

Abstract: Heterotrimeric G-proteins along with G-protein-coupled receptors (GPCRs) regulate many biochemical functions by relaying the information from the plasma membrane to the inside of the cell. The lipid modifications of Gα and Gγ subunits, together with the charged regions on the membrane interaction surface, provide a peculiar pattern for various heterotrimeric complexes. In a previous study, we found that Gαs and Gαi3 prefer different types of membrane-anchor and subclass-specific lipid domains. In the present r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 55 publications
3
20
1
Order By: Relevance
“…The cells were observed using Leica SP5 II SMD confocal microscope with an integrated module PicoHarp 300 Time-Correlated Single Photon Counting (TCSPC) system (PicoQuant, Berlin, Germany). The experiments were conducted as described earlier in detail [34]. Confocal images of the cells were collected prior to each FLIM measurement.…”
Section: Flim-fret Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cells were observed using Leica SP5 II SMD confocal microscope with an integrated module PicoHarp 300 Time-Correlated Single Photon Counting (TCSPC) system (PicoQuant, Berlin, Germany). The experiments were conducted as described earlier in detail [34]. Confocal images of the cells were collected prior to each FLIM measurement.…”
Section: Flim-fret Measurementsmentioning
confidence: 99%
“…caveolins) [31,32]. Moreover, the specific membrane targeting of G proteins is affected by the Gβγ dimer which seems to determine the preference toward the lessordered segments of the lipid bilayer [31,33,34]. These observations indicate that localization may change in different states of the signal transduction process when the G protein trimer dissociates or associates.…”
mentioning
confidence: 99%
“…Co-translational and post-translational lipid modifications in proteins are critical to influence protein-lipid interactions, fulfilling roles above and beyond the mere binding of the protein to the lipid bilayer [27]. These modifications contribute to the peripheral and transmembrane localization of proteins at/in specific organelle membranes and membrane regions or microdomains [9,21,23,[28][29][30]. In addition, certain amino acid domains in proteins that drive their binding to lipids influence their mobilization from the aqueous to particulate (membrane) compartments.…”
Section: How Protein Structure Influences Protein-lipid Interactionsmentioning
confidence: 99%
“…In contrast, inhibitory Gia subunits block AC activation, thereby limiting cyclic AMP production. An elegant study in this Special Edition explores the role of the gamma subunits in the regulation of localization and activation of Gsα and Giα, while using FRET and mobility measurements [ 11 ]. It was shown that the rate of G-protein diffusion depends on the subclass of γ-subunit, and Gsα and Giα exhibited different behaviours [ 11 ].…”
Section: Control Of Cyclic Amp Synthesismentioning
confidence: 99%
“…An elegant study in this Special Edition explores the role of the gamma subunits in the regulation of localization and activation of Gsα and Giα, while using FRET and mobility measurements [ 11 ]. It was shown that the rate of G-protein diffusion depends on the subclass of γ-subunit, and Gsα and Giα exhibited different behaviours [ 11 ]. This has relevance for the sequestration of cyclic AMP signalling to discrete sub-cellular compartments, or “nanodomains”, which is now widely viewed as the paradigm for “compartmentalised” cellular signalling in biological systems.…”
Section: Control Of Cyclic Amp Synthesismentioning
confidence: 99%